(untitled) (International Journal of Food and Nutritional Sciences, 2022)
E-Commerce means business efficiency at all operation levels. It does not just mean trading and shopping on the Internet. The SCM is the backbone of E-Commerce also a very critical component of E-Commerce. The study on the impact of Supply chain on E Commerce aims to explain the efficiency of E-Commerce in industrial supply chain management, how effectively E-Commerce is applied on industries and the functions of supply chain management. The study explains the different types of technology for supporting E-Commerce, servers in the present and future content. To understand and develop the E-Commerce and supply chain management. The research methodology adopted for the study is of a descriptive type.